EVALUATION OF FROZEN EMBRYO TRANSFER OUTCOMES FOLLOWING NATURAL CYCLE PROTOCOL AT HANOI MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of frozen embryo transfer cycles in which endometrial preparation was performed using a natural cycle protocol in women with regular menstrual cycles.Materials and methods: A retrospective descriptive study was conducted on patients undergoing in vitro fertilization treatment at Hanoi Medical University Hospital.Results: A total of 124 patients were included, comprising 63 natural cycles and 61 hormone replacement therapy cycles. The two groups were comparable in age, BMI, duration of infertility, and ovarian reserve parameters. The clinical pregnancy and ongoing pregnancy rates were 55.6% and 49.2% in the natural cycle group, respectively, comparable to 54.1% and 45.9% in the hormone replacement therapy group (p > 0.05). The incidence of first-trimester bleeding was significantly lower in the natural cycle group compared with the hormone replacement therapy group (11.1% vs. 34.4%; p < 0.05).Conclusion: In women with regular menstrual cycles, frozen embryo transfer cycles prepared with a natural cycle protocol achieved similar pregnancy outcomes compared with hormone replacement therapy cycles but were associated with fewer early pregnancy complications.
Keywords: Frozen embryo transfer, natural cycle, hormone replacement therapy, in vitro fertilization.